A JUZ A DAY : Summary of the Quran - Yahya Ibrahim (Tertib Publishing, 2020)
The Qur’an refers to a wealth of human experience, seeking to enrich our lives on earth before our eventual return to our Maker, the Most High. Although it is impossible to articulate a translation that establishes clearing the majestic nature of the Qur’an in any language of the world, nevertheless, Muslims need to become more familiar with the overall coherence of its message in their native language. The aim of this work before you is to highlight key themes and messages of the Qur’an that will be recited throughout our lives so those who are not able to understand the Arabic reading can feel a connection with what they will hear and recite by reading this summation.